Amide-containing neoepitopes: the key factor in the preparation of hapten-specific antibodies and a strategy to overcome - Han, Xiangning; Lin, Hong; Chen, Xiangfeng; Wang, Luefeng; Zhang, Ziang; Wei, Xiaojing; Sun, Xun; Xie, Hanyi; Pavase, Tushar Ramesh; Cao, Limin; Sui, Jianxin (Frontiers in Immunology, 2023)
For a long time, people have suffered from uncertainty, complexity, and low success rate in generating and screening antibodies against small molecules, which have become the core bottlenecks of immunochemistry. Here, the influence of antigen preparation on antibody generation was investigated at both molecular and submolecular levels. Neoepitopes (amide-containing neoepitopes) formed in the preparation complete antigen is one of the most important factors limiting the efficiency of generating hapten-specific antibodies which was verified by different haptens, carrier proteins and conjugation conditions. Amide-containing neoepitopes present electron-dense structural components on the surface of prepared complete antigens and, therefore, induce the generation of the corresponding antibody with much higher efficiency than target hapten. Crosslinkers should be carefully selected and not overdosed. According to these results, some misconceptions in the conventional anti-hapten antibody production were clarified and corrected. By controlling the content of EDC (1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) during synthesis of immunogen to limit the formation of amide-containing neoepitopes, the efficiency of hapten-specific antibody generation could be significantly improved, which verified the correctness of the conclusion and provided an efficient strategy for antibody preparation. The result of the work is of scientific significance in preparation high-quality antibody against small molecules.